2010
DOI: 10.4238/vol9-2gmr755
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of ACE gene I/D polymorphism with obstructive sleep apnea syndrome in Turkish patients

Abstract: ABSTRACT. Angiotensin-converting enzyme (ACE) is a vital enzyme in the renin-angiotensin-aldosterone system, and there are reports in the literature describing its role in the development of cardiovascular system diseases, with I/D polymorphism of the ACE gene. We examined the relationship between a patient group with obstructive sleep apnea syndrome (OSAS) and a control group in terms of I/D polymorphism of the ACE gene. We examined 64 patients, with 37 individuals serving as the control group. PCR was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Based on our search strategy, the primary screening produced 21 potentially relevant articles, of which 15 met the inclusion criteria as an attempt to evaluate the association between the ACE I/D polymorphism and occurrence of OSAHS (Xiao et al, 1999;Zhang et al, 2000;Barcelo et al, 2001;Ping et al, 2001;Li et al, 2004a,b;Lin et al, 2004;Zhang et al, 2004;Gu et al, 2006;Li et al, 2006;Bostrom et al, 2007;Benjamin et al, 2008;Koyama et al, 2009;Ogus et al, 2010;Yakut et al, 2010). A total of 1361 OSAHS patients and 1373 controls were analyzed.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our search strategy, the primary screening produced 21 potentially relevant articles, of which 15 met the inclusion criteria as an attempt to evaluate the association between the ACE I/D polymorphism and occurrence of OSAHS (Xiao et al, 1999;Zhang et al, 2000;Barcelo et al, 2001;Ping et al, 2001;Li et al, 2004a,b;Lin et al, 2004;Zhang et al, 2004;Gu et al, 2006;Li et al, 2006;Bostrom et al, 2007;Benjamin et al, 2008;Koyama et al, 2009;Ogus et al, 2010;Yakut et al, 2010). A total of 1361 OSAHS patients and 1373 controls were analyzed.…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 1361 OSAHS patients and 1373 controls were analyzed. Of these 15 articles, 9 (Xiao et al, 1999;Zhang et al, 2000;Barcelo et al, 2001;Lin et al, 2004;Bostrom et al, 2007;Benjamin et al, 2008;Koyama et al, 2009;Ogus et al, 2010;Yakut et al, 2010) were published in English and 6 in Chinese (Ping et al, 2001;Li et al, 2004a,b;Zhang et al, 2004;Gu et al, 2006;Li et al, 2006). The detailed selection process is presented in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Evidence has shown that genetic determinants of upper-airway muscle activity, craniofacial structure, obesity, fat distribution, and respiratory control may interact and cause OSA (Casale et al, 2009). Most genetic association studies have focused on the TNF-α, ACE I/D, and APOE genes (Cosentino et al, 2008;Popko et al, 2008;Bhushan et al, 2009;Yakut et al, 2010). Bhushan et al (2009) reported that the frequency of the TNF-α (-308A) allele and serum TNF-α levels were significantly higher in obese Asian Indians with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, IRS gene polymorphisms were investigated in glucose metabolism disorders [27,28]. In a study, Bayazit et al [28] suggested that the polymorphism of the IRS-1 gene at codon 972, especially Gly/Arg variant or the presence of the allele for Arg appears to be associated with occurrence of OSAS in male patients, whereas this polymorphism is not related to severity of OSAS.…”
Section: Medicine Science 2013;2(4):830-41 Irs Gene Polymorphism In Omentioning
confidence: 99%